Event-Triggered H∞ Filtering for Markovian Jump Neural Networks under Random Missing Measurements and Deception Attacks - Jinxia Wang; Jinfeng Gao; Tian Tan; Jiaqi Wang; Miao Ma (Complexity)
This paper concentrates on the event-triggered H∞ filter design for the discrete-time Markovian jump neural networks under random missing measurements and cyber attacks. Considering that the controlled system and the filtering can exchange information over a shared communication network which is vulnerable to the cyber attacks and has limited bandwidth, the event-triggered mechanism is proposed to relieve the communication burden of data transmission. A variable conforming to Bernoulli distribution is exploited to describe the stochastic phenomenon since the missing measurements occur with random probability. Furthermore, seeing that the communication networks are vulnerable to external malicious attacks, the transferred information via the shared communication network may be changed by the injected false information from the attackers. Based on the above consideration, sufficient conditions for the filtering error system to maintain asymptotically stable are provided with predefined H∞ performance. In the end, three numerical examples are given to verify the proposed theoretical results.